Refractive errors in students from Middle Eastern backgrounds living and undertaking schooling in Australia. - Azizoglu, S; Junghans, B; Barutchu, A; Crewther, S (2011)
BACKGROUND:   Environmental factors associated with schooling systems in various countries have been implicated in the rising prevalence of myopia, making the comparison of prevalence of refractive errors in migrant populations of interest. This study aims to determine the prevalence of refractive errors in children of Middle Eastern descent, raised and living in urban Australia but actively maintaining strong ties to their ethnic culture, and to compare them with those in the Middle East where myopia prevalence is generally low. METHODS:   A total of 354 out of a possible 384 late primary/early secondary schoolchildren attending a private school attracting children of Middle Eastern background in Melbourne were assessed for refractive error and visual acuity. A Shin Nippon open-field NVision-K5001 autorefractor was used to carry out non-cycloplegic autorefraction while viewing a distant target. For statistical analyses students were divided into three age groups: 10-11 years (n = 93); 12-13 years (n = 158); and 14-15 years (n = 102). RESULTS:   All children were bilingual and classified as of Middle Eastern (96.3 per cent) or Egyptian (3.7 per cent) origin. Ages ranged from 10 to 15 years, with a mean of 13.17 ± 0.8 (SEM) years. Mean spherical equivalent refraction (SER) for the right eye was +0.09 ± 0.07 D (SEM) with a range from -7.77 D to +5.85 D. The prevalence of myopia, defined as a spherical equivalent refraction 0.50 D or more of myopia, was 14.7 per cent. The prevalence of hyperopia, defined as a spherical equivalent refraction of +0.75 D or greater, was 16.4 per cent, while hyperopia of +1.50 D or greater was 5.4 per cent. A significant difference in SER was seen as a function of age; however, no significant gender difference was seen. CONCLUSIONS:   This is the first study to report the prevalence of refractive errors for second-generation Australian schoolchildren coming from a predominantly Lebanese Middle Eastern Arabic background, who endeavour to maintain their ethnic ties. The relatively low prevalence of myopia is similar to that found for other metropolitan Australian school children but higher than that reported in the Middle East. These results suggest that lifestyle and educational practices may be a significant influence in the progression of myopic refractive errors.